Efektivitas Bimbingan Kelompok dengan Metode Problem Solving dalam Mengatasi Konflik antar Pribadi pada Siswa Kelas 10 - Nila Dati Saidati; Muslikah, Muslikah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study aims to analyze the effectiveness of group guidance services using the problem-solving method in addressing interpersonal conflicts among 10th-grade students. The study employs a Systematic Literature Review (SLR) approach to synthesize empirical findings comprehensively, including stages such as formulating research questions, determining keywords, searching literature through Google Scholar, Portal Garuda, and accredited guidance and counseling journals, selecting articles based on inclusion and exclusion criteria, assessing study quality, extracting data, and conducting narrative synthesis analysis. The inclusion criteria consist of original research articles published within the last five to ten years focusing on group guidance, problem-solving methods, interpersonal conflicts, and secondary school students, while irrelevant studies, those lacking clear intervention procedures, or not focusing on secondary school students are excluded. The results indicate that group guidance with the problem-solving method is effective in enhancing students’ ability to identify root causes of problems, manage emotions, develop assertive communication, and formulate rational and cooperative solutions to peer conflicts, as well as improving self-efficacy, emotional intelligence, learning motivation, positive self-concept, and reducing aggressive behavior. Therefore, it is recommended that guidance and counseling teachers integrate the problem-solving method in a structured, continuous, and contextual manner within group services to support students’ social, emotional, and academic development.